Frog music [large type] : a novel - Donoghue, Emma, 1969- (Little, Brown and Company, 2014)
Summer of 1876: San Francisco is in the fierce grip of a record-breaking heat wave and a smallpox epidemic. Through the window of a railroad saloon, a young woman named Jenny Bonnet is shot dead. The survivor, her friend Blanche Beunon, is a French burlesque dancer. Over the next three days, she will risk everything to bring Jenny's murderer to justice -- if he doesn't track her down first. The story Blanche struggles to piece together is one of free-love bohemians, desperate paupers, and arrogant millionaires; of jealous men, icy women, and damaged children. It's the secret life of Jenny herself, a notorious character who breaks the law every morning by getting dressed: a charmer as slippery as the frogs she hunts. (Based on a true story.)